Multinodular Goiter Spontaneous Hemorrhage in ESRD Patients Result in Acute Respiratory Failure: A Case Report. Issue 6 (February 2016) - Lei, Wen-Hui; Shao, Chu-Xiao; Xin, Jun; Li, Jie; Mao, Ming-Feng; Yu, Xue-Ping; Jin, Lie
Abstract : Abstract: Euthyroid multinodular goiters may lead to acute respiratory failure caused by airway obstruction or laryngotracheal compression. Here, we present a case admitted to the nephrologist with multinodular goiter spontaneous hemorrhage along with respiratory failure and end-stage renal disease (ESRD), which required urgent surgical intervention. We report the case of a 63-year-old woman with ESRD who presented with a rapidly enlarging nodular goiter resulting in acute respiratory failure. Endotracheal intubation and emergency partial thyroidectomy were performed, revealing multinodular goiter spontaneous hemorrhage by postoperative histopathology. Several cases of benign goiters necessitating endotracheal intubation have been reported. Goiters are among the rare diagnoses in patients consulting at our institution's Nephrology. This case illustrates that ESRD patients with benign goiter may lead to acute respiratory failure due to airway obstruction or laryngotracheal compression. It was found in agreement with previous reports. This case highlights that ESRD patient at risk of this life threatening complication such as multinodular goiter hemorrhage should be managed with elective thyroidectomy to reduce morbidity and mortality.